Effect of Ion-Induced Electrons Emission on the Plasma Sheath Voltage - Khanal, R (Scientific World, 2010)
The effect of ion-induced electrons emission on the plasma sheath voltage for different values of ion induced electrons emission coefficients has been studied. Using a Kinetic Trajectory Simulation model of plasma sheaths, we calculate the particle densities reaching the wall and for given ion induced electrons emission coefficient the additional electrons emitted from the wall is obtained. Finally, the plasma sheath voltage (wall potential) is obtained by solving the Poisson equation. It has been observed that the potential decreases as the ion-induced electron emission coefficient increases as expected theoretically. Key words: Plasma; Quasineutrality; Debye Shielding; Sheath; Presheath; Bohm criterion. DOI: 10.3126/sw.v6i6.2625 Scientific World, Vol. 6, No. 6, July 2008 4-7